Shanghai and the edges of empires. - Meng, Yue, 1956- (Univ Of Minnesota Press, 2006)
Shanghai and the Edges of Empires analyzes a century-long shift of urbanity from Chinas heartland to its shore. Simultaneously appropriating and resisting imposing forces, Shanghai opened itself to subversive practices, becoming a crucible of creativity and modernism. Meng Yue reveals the paradoxical interdependence between imperial and imperialist histories and the retranslation of culture that characterized the emergence of the city of Shanghai.